Use of ZnO thin films as sacrificial templates for metal organic vapor phase epitaxy and chemical lift-off of GaN - Rogers, D.J. (2007)
Continued development of GaN-based light emitting diodes is being hampered by constraints imposed by current non-native substrates. ZnO is a promising alternative substrate but it decomposes under the conditions used in conventional GaN metal organic vapor phase epitaxy MOVPE . In this work, GaN was grown on ZnO/c-Al2O3 using low temperature/pressure MOVPE with N2 as a carrier and dimethylhydrazine as a N source. Characterization confirmed the epitaxial growth of GaN. The GaN was lifted-off the c-Al2O3 by chemically etching away the ZnO underlayer. This approach opens up the way for bonding of the GaN onto a support of choice. © 2007 American Institute of Physics